A novel methodology for engine design and optimization. (4th August 2014) - Karvounis, E.; Assanis, D.
A novel methodology towards computer–aided design and optimisation of internal combustion engines is introduced. Existing models of engine components and processes are integrated into a multi–purpose, flexible configuration framework. Fundamental thermodynamic elements, including zero–dimensional control volumes, one–dimensional pulsating fluid lines, and continuous flow machines, are identified as the constituent components of engine systems. Models of the behaviour of these elements, with various degrees of thermodynamic resolution, have been implemented into the framework. Thermodynamic models are supplemented by phenomenological models of combustion heat release and heat transfer processes. Provisions are also made so that user–supplied models of components and processes may be linked to the code with minimal programming effort. The task of the engine designer is, thus, reduced into selecting appropriate thermodynamic elements to model the engine system based on his/her design objectives. The applicability of the present methodology to a wide range of simulation problems is demonstrated.